Assessing the lifetime of anthropogenic CO2 and its sensitivity to different carbon cycle processes - C. Kaufhold; C. Kaufhold; M. Willeit; B. Liu; B. Liu; A. Ganopolski (Biogeosciences)
Although it is well-established that anthropogenic CO2 emitted into the atmosphere will persist for a long time, the duration of the anthropogenic climate perturbation will depend on how rapidly the excess CO2 is removed from the climate system by different biogeochemical processes. The uncertainty around the long-term climate evolution is therefore linked to not only the future of anthropogenic CO2 emissions but also our insufficient understanding of the long-term carbon cycle. Here, we use the fast Earth system model CLIMBER-X, which features a comprehensive carbon cycle, to examine the lifetime of anthropogenic CO2 and its effects on the long-term evolution of atmospheric CO2 concentration. This is done through an ensemble of 100 000-year-long simulations, each driven by idealized CO2 emission pulses. Our findings indicate that depending on the magnitude of the emission, 75 % of anthropogenic CO2 is removed within 197–1820 years of the peak CO2 concentration (with larger cumulative emissions taking longer to remove). Approximately 4.3 % of anthropogenic CO2 will remain beyond 100 kyr. We find that the uptake of carbon by land, which has only been considered to a small extent in previous studies, has a significant long-term effect, storing approximately 4 %–13 % of anthropogenic carbon by the end of the simulation. Higher-emission scenarios fall on the lower end of this range, as increased soil respiration leads to greater carbon loss. For the first time, we have quantified the effect of dynamically changing methane concentrations on the long-term carbon cycle, showing that its effects are likely negligible over long timescales. The timescale of carbon removal via silicate weathering is also reassessed here, providing an estimate (80–105 kyr) that is significantly shorter than some previous studies due to higher climate sensitivity, stronger weathering feedbacks, and the use of a spatially explicit weathering scheme, leading to faster removal of anthropogenic CO2 in the long term. Furthermore, this timescale is shown to have a non-monotonic relationship with cumulative emissions. Our study highlights the importance of adding model complexity to the global carbon cycle in Earth system models to accurately represent the long-term future evolution of atmospheric CO2.